You don't own me [compact disc, unabridged] - Clark, Mary Higgins; Burke, Alafair (Clark, Mary Higgins. Under suspicion., 2018)
When TV producer Laurie Moran investigates an unsolved murder, she becomes entangled in a web of long-buried secrets and begins to wonder if her own life is in grave danger as a mysterious stalker plots revenge.